Instalación e Implementación de un Panel Fotovoltaico Aprovechamiento en un Vivienda Familiar en la Vereda Siquitan del Municipio de Tangua. (2022)
The article describes the design and construction process of a hand washing prototype for children between 3 and 8 years of age, in order to improve their health conditions in a playful way. To do this, it begins with the specification of the design requirements, among which are: small size, easy transport, bright colors and safe hand washing. The process of measuring the soap dosage, washing and drying times continues, which will serve as a reference for the programming of the Arduino microcontroller. Also included is the mechanical design of the structure and of the soap and water pumping systems. Finally, the construction process and the tests to verify the functionality of the prototype are described.